The Chinese middle class an analysis of its political influence towards democracy in China. - Wong, Andrea Chloe (2008)
Prior to the reforms of the 1980s, China was a largely egalitarian and highly impoverished country. However, after decades of economic reforms, China is currently richer and less egalitarian than it was in the past. Proof of this development is the emergence of the "new rich" or the middle class in China. Their existence has been the object of media attention in recent years. There is much journalistic hype about this group's economic influence and spending power that affect China's economy and society. Members of the Chinese middle class are portrayed as the hard-working entrepreneurs and professionals thriving in the bustling cities of China. They possess sophisticated tastes in consumption and share materialistic values and affluent lifestyles. Meanwhile, Chinese scholars and China observers pay attention to this group's likely political influence in the country. As members of the middle class in China increase over the years, analysts assume that this group will not only influence the socio-economic sphere in the country. The emergence and expansion of the Chinese middle class are perceived to carry political implications that may affect the dominance of the party-state. More specifically, they are perceived as possible agents of democracy in the country, similar to the other middle classes in democratic societies in the West and in some countries in Asia. Despite this widely held assumption, this paper reveals that this will not be the case for the Chinese middle class, at latest not in the near future. They are generally content with the political status quo and will not advocate for democracy in the country.
"March 2008."
Vita.
Thesis--(M.A. Asian Studies), University of the Philippines Diliman.
Keywords: Middle class -- China; Middle class -- Political activity -- China; Middle class -- China -- Economic conditions